Congenital Medial Clavicular Pseudoarthrosis - A Rare Presentation in an Adult - Mohd Ilyas; Brijesh Puthalonkunath Valsalan (Dr. Annil Mahajan, 2024)
We are presenting a rare case of a 29-year-old male patient with congenital pseudoarthrosis of the clavicle who presented in adulthood with a progressively growing lump on medial end of clavicle which after investigations tuned out to be pseudoarthrosis of the medial clavicle.